(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2025)
This study aimed to evaluate the extent of application of the elements of the pharmaceutical marketing mix practiced by pharmaceutical companies and warehouses on the Syrian coast. In its evaluation, the researcher relied on five dimensions of the pharmaceutical marketing mix (pharmaceutical product, pharmaceutical promotion, pharmaceutical pricing, pharmaceutical distribution, and pharmaceutical operations). The researcher relied on the analytical approach, and also relied on the facilitated random sampling method, where the questionnaire was distributed to a sample of 117 individuals from doctors and pharmacists dealing with the companies and warehouses studied, and appropriate statistical tests were conducted, including simple linear correlation, and a one-sample difference test. The researcher reached a set of results: • There is an application for the pharmaceutical product, pharmaceutical promotion, and pharmaceutical distribution by the companies and warehouses studied. • There is no application for pharmaceutical distribution in the form required by the companies and warehouses studied. • The sample tended to be neutral towards the application of pharmaceutical operations by the studied drug companies and warehouses.